Aedes aegypti SGS1 is critical for Plasmodium gallinaceum infection of both the mosquito midgut and salivary glands - Bianca B. Kojin; Ines Martin-Martin; Helena R. C. Araújo; Brian Bonilla; Alvaro Molina-Cruz; Eric Calvo; Margareth L. Capurro; Zach N. Adelman (Malaria Journal, 2021)
Abstract Background The invasion of the mosquito salivary glands by Plasmodium sporozoites is a critical step that defines the success of malaria transmission and a detailed understanding of the molecules responsible for salivary gland invasion could be leveraged towards control of vector-borne pathogens. Antibodies directed against the mosquito salivary gland protein SGS1 have been shown to reduce Plasmodium gallinaceum sporozoite invasion of Aedes aegypti salivary glands, but the specific role of this protein in sporozoite invasion and in other stages of the Plasmodium life cycle remains unknown. Methods RNA interference and CRISPR/Cas9 were used to evaluate the role of A. aegypti SGS1 in the P. gallinaceum life cycle. Results Knockdown and knockout of SGS1 disrupted sporozoite invasion of the salivary gland. Interestingly, mosquitoes lacking SGS1 also displayed fewer oocysts. Proteomic analyses confirmed the abolishment of SGS1 in the salivary gland of SGS1 knockout mosquitoes and revealed that the C-terminus of the protein is absent in the salivary gland of control mosquitoes. In silico analyses indicated that SGS1 contains two potential internal cleavage sites and thus might generate three proteins. Conclusion SGS1 facilitates, but is not essential for, invasion of A. aegypti salivary glands by P. gallinaceum and has a dual role as a facilitator of parasite development in the mosquito midgut. SGS1 could, therefore, be part of a strategy to decrease malaria transmission by the mosquito vector, for example in a transgenic mosquito that blocks its interaction with the parasite.